PROLINE AND SPECIFIC ROOT LENGHT AS RESPONSE TO DROUGHT OF WHEAT LINES (Triticum aestivum L.) - Nunun Barunawati; Moch. Dawam Maghfoer; Niken Kendarini; Nurul Aini (AGRIVITA, Journal of Agricultural Science, 2016)
The national wheat imported reaches approx.-imately 7 million ton per year, recently. The wheat plantation in Indonesia is strongly affected by the high temperature which triggers the stunned roots. Thus the plan wheat growth and production reduced. The experiment to investigate of selected-local wheat lines which were already established in Indonesia and resistant to drought effect. The level of drought influence on several growth parameters of vegetative plant and thus affected to seeds production as well as on total yield. The results show that the introduced-variety of wheat line, SO3 shows the significant tolerant to drought and able to maintain the SRL (specific root length) and increase the proline contents to with stand the drought condition compare to other lines (M7 and M8). The proline as amino acid climbed extremely effected by drought, in contrast the root growth in particular their length reduced. Those plant conditions influence the plant vegetative growth and generative phases, especially for seed production. Additionally, the M8 and SO3 selected-line presents the stability on yield production compare to other varieties, since it able maintain the content of proline and ratio of root length. Therefore, those selected lines are appropriate to grow in Indonesia which produces at approximately 3.5 t ha-1.